2013
DOI: 10.1509/jmr.11.0342
|View full text |Cite
|
Sign up to set email alerts
|

Look at Me! Look at Me! Conspicuous Brand Usage, Self-Brand Connection, and Dilution

Abstract: Conspicuous brand usage, defined as attention-getting use of a brand, causes brand dilution under certain conditions. This research examines changes in observers' attitudes toward a brand after seeing a brand user engaged in conspicuous use of the brand. The authors propose that observers infer that a consumer engaged in conspicuous brand usage is driven by an ulterior motive of impression management. When observers have low self-brand connection, they exhibit less favorable attitudes toward both the brand use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 29 publications
5
128
2
1
Order By: Relevance
“…Table of Based on the above estimates, conspicuousness, self-brand connection and the interaction: conspicuousness × self-brand connection, significantly affect the attitude towards the brand, consistent with Ferraro et al (2013). Note that since since there are continuous covariates, a type III analysis of variance is used, so that the sum of squares (and effect size) for each effect is computed conditional upon all other effects.…”
Section: R> Summary(app_3)supporting
confidence: 58%
See 3 more Smart Citations
“…Table of Based on the above estimates, conspicuousness, self-brand connection and the interaction: conspicuousness × self-brand connection, significantly affect the attitude towards the brand, consistent with Ferraro et al (2013). Note that since since there are continuous covariates, a type III analysis of variance is used, so that the sum of squares (and effect size) for each effect is computed conditional upon all other effects.…”
Section: R> Summary(app_3)supporting
confidence: 58%
“…In this application we illustrate a between-subjects BANOVA, with dependent variables that are, respectively normal and ordered categorical. The second study, by Ferraro, Kirmani, and Matherly (2013), examines the effects of conspicuous brand usage on consumers' attitudes toward a brand. In this application, we illustrate hierarchical BANOVA models, with continuous covariates normal and t distributed dependent variables.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we test whether positive effects on non-involved consumers' perceptions also apply for wellestablished brands. For this purpose, we consider smartphones to be a particularly interesting product category, as it has been shown that consumers use smartphone brands, especially Apple products, to signal high status (Ferraro et al, 2013). Thus, the potential effects will be tested in a product category in which the brand is supposed to influence the purchase process of many consumers in order to see whether a positive effect on the perceived innovation ability and behavioural intentions can still be found.…”
Section: Meißner M D Haurand and C Stummermentioning
confidence: 99%